2015
DOI: 10.3329/jesnr.v6i1.22048
|View full text |Cite
|
Sign up to set email alerts
|

Status of Fisheries Resources and Water Quality of Tanguar Haor

Abstract: Abstract:The study was conducted to observe the status of fisheries resource of Tanguar haor, one of the large wetland in the north eastern part of Bangladesh. For this purpose the whole study was completed in two parts: interviewing with local people and analyzing the water quality. Indiscriminate harvesting of mother fishes, use of agrochemicals, sedimentation on haor basin and habitat destruction were found as major causes of fisheries resources degradation in the study area. Most of the water quality param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…The water temperature among all the sampling stations of Tanguar haor ranged from 27.2°C to 29.4°C with a mean value of 28.28°C. Similar mean value of temperature (27.98°C) was found by Mamun et al (2013) from Tanguar haor water. Average pH of the water samples ranged from 7.3 to 8.7.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The water temperature among all the sampling stations of Tanguar haor ranged from 27.2°C to 29.4°C with a mean value of 28.28°C. Similar mean value of temperature (27.98°C) was found by Mamun et al (2013) from Tanguar haor water. Average pH of the water samples ranged from 7.3 to 8.7.…”
Section: Resultssupporting
confidence: 83%
“…Averages DO of the water sample ranged from 4.27 mg L −1 to 8.56 mg L −1 . But Mamun et al (2013) found the highest DO value was 5.5 mg L −1 at Majampur and the lowest value was 4.5 mg L −1 at Hoirakuna. Normal TDS of the water samples ranged from 731 to 1020 mg L −1 .…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Recently, Bhuiyan et al (2017) reported the mean concentration of soluble reactive phosphorus (SRP) for the Haor as 16.3 μg/l and nitrate-nitrogen as 180 μg/l. Mamun et al (2013) reported water temperature, pH and dissolved oxygen (DO) as 28.0°C, 7.32 and 5.03 mg/l, respectively which is quite consistent with the findings of Bhuiyan et al (2017). The water of Tanguar Haor could be classified as alkaline with moderate concentrations of SRP and nitrate-nitrogen.…”
Section: Resultssupporting
confidence: 89%